Membangun Kinerja Organisasi Melalui Komunikasi Interpersonal pada Organisasi Bisnis Pendidikan di Kota Pekanbaru - masirun, masirun (Jurnal Daya Saing, 2016)
Business organizations are effective in achieving its objectives requires the power of communication both owned personally and of the organization itself. This study proves that using the case of the commercial business organizations in the city of Pekanbaru with the use of a sample of educators as many as 56 people in the census and data collection using questionnaires and analyzed with simple regression showed that the interpersonal communication significantly influence the performance of the business organization. Keywords: organizational performance, interpersonal communication